2016
DOI: 10.1021/acscatal.5b02766
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Preferences of a Tropos Biphenyl Phosphinooxazoline–a Ligand with Wide Substrate Scope

Abstract: Excellent enantioselectivities are observed in palladium-catalyzed allylic substitutions of a wide range of substrate types and nucleophiles using a bidentate ligand composed of oxazoline and chirally flexible biaryl phosphite elements. This unusually wide substrate scope is shown by experimental and theoretical studies of its η 3 -allyl and η 2 -olefin complexes not to be a result of configurational interconversion of the biaryl unit, since the ligand in all reactions adopts an S a ,S configuration on coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 108 publications
0
35
1
1
Order By: Relevance
“…Phosphorochloridites were easily prepared in one step from the corresponding biaryl alcohols . Compounds 2 , 3 – 6 , 7 , 8 ; ligands L1 – L4a , L1b – L1c , L1f – g , and L3 – L6b ; and complexes [Ir(cod)( L )]BAr F ( L = L1a – c , L3a — c and L4 – L6b ) were prepared as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorochloridites were easily prepared in one step from the corresponding biaryl alcohols . Compounds 2 , 3 – 6 , 7 , 8 ; ligands L1 – L4a , L1b – L1c , L1f – g , and L3 – L6b ; and complexes [Ir(cod)( L )]BAr F ( L = L1a – c , L3a — c and L4 – L6b ) were prepared as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, we found that replacing the phosphine moiety in phosphine‐oxazoline PHOX ligands by a biaryl phosphite moiety not only improved activity but also increased substantially the substrate scope in the Pd‐allylic substitution and the Ir‐catalyzed hydroboration . The reason for this exceptional performance is the flexiblility of the biaryl phosphite group that allows the chiral pocket of the catalyst to accommodate itself according to the steric demands of the substrate . Moreover, their easy preparation from alcohols and their higher stability towards air and other oxidizing agents than other commonly used phosphines make phosphite ligands very attractive ,.…”
Section: Introductionmentioning
confidence: 99%
“… 2016 6 1701 1712 . 3 The unusually wide substrate scope of the ligand was shown to be a result of its ability to change the size of the substrate-binding pocket.…”
Section: Key Referencesmentioning
confidence: 99%
“…In this context, we have shown the benefits of using heterodonor biaryl phosphite‐oxazoline ligand families for the Ir‐catalyzed hydrogenation of minimally functionalized olefins, which in the last decades have become the state of art for the reduction of these challenging substrates . We have also recently found that the previously mentioned PHOX‐based phosphate‐oxazoline ligands can be considered privileged ligands not only for their ability to control the stereochemistry in the Ir‐catalyzed hydrogenation, with a exceptionally broad substrate scope, but also because they work well in a variety of processes, such as Pd‐catalyzed Heck and allylic substitution reactions and Ir‐catalyzed hydroboration . The reason for this exceptional performance is the flexible biaryl phosphite group that allows the chiral pocket of the catalyst to accommodate itself according to the steric demands of the substrate .…”
Section: Introductionmentioning
confidence: 99%
“…We have also recently found that the previously mentioned PHOX‐based phosphate‐oxazoline ligands can be considered privileged ligands not only for their ability to control the stereochemistry in the Ir‐catalyzed hydrogenation, with a exceptionally broad substrate scope, but also because they work well in a variety of processes, such as Pd‐catalyzed Heck and allylic substitution reactions and Ir‐catalyzed hydroboration . The reason for this exceptional performance is the flexible biaryl phosphite group that allows the chiral pocket of the catalyst to accommodate itself according to the steric demands of the substrate . Moreover, phosphite ligands are less sensitive to air and other oxidizing agents and also easier to prepare than the most commonly used phosphines, which have dominated the field of asymmetric hydrogenation.…”
Section: Introductionmentioning
confidence: 99%